Laparoscopic management of vesicouterine fistula following vaginal delivery and caesarean section in the past medical history: a case report - Wojciech Ordon; Beata Antosiak; Paweł Pawłowicz; Jarosław Cieślak; Andrzej Malinowski (Menopause Review, 2010)
Authors report a case of a vesicouterine fistula of a 38–year-old patient. The disease presented on thesecond day after physiological delivery in very early puerperium, the patient complains of urinary leakage fromvagina. In the past medical history, the patient had a caesarean section 4 years ago.Laparoscopy was performed to close the fistula three months after the delivery. The bladder wall wasprepared and mobilized from the vesico-utero space. The fistula was closed by single stitches. We achievedcomplete closing of the vesicouterine fistula and fistula symptoms were gone. Delayed laparoscopy was theproper operation to repair the vesicouterine fistula.Use of laparoscopy techniques in operating genitourinary fistulas gives very satisfactory results. In theliterature, laparoscopy vesicouterine fistula closure is presented as a safe intraperitoneal surgery that is lessinvasive than traditional.In the authors’ view, laparoscopy is a successful and very safe method of closure of vesicouterine fistulas.